Reconstructing star dune dynamics using ground penetrating radar: how movement shapes complex surface structures - Herzog, Manuel; Schmitt, Alexander; Bubenzer, Olaf (Aeolian research, 2024)
The evolution of large star dunes, because of their remote location, size and surface complexity, is barely recorded and understood. This lack of understanding applies to surface and subsurface features alike. In order to detect the transformation, the detailed subsurface stratigraphy and the relative chronology of large star dunes, we used ground penetrating radar (GPR) on all major arms of a complex star dune of Erg Chebbi, south-eastern Morocco. We used a 350 MHz digital antenna from Geophysical Survey Systems, Inc (GSSI), reaching a depth of 12.5 m to identify main radar facies associated with former downwind dune flanks describing the depositional history. Our results enable the determination of former dune crest positions, their potential past movement and in consequence the construction of the paleo-dune topography. In accordance with simulated historical wind data, we found a potential sediment deficit on the south-eastern side of the dune. This also correlates with surface data describing an oblique form of the star dune and the spatial distribution frequency of its major arms. Our detailed recordings show, for the first time, the complex internal composition of all arms of one large star dune and surface sensitive form-flow interactions. Our results allow the discrimination of deposition phases and therefore, we have constructed a relative chronology as a basis for future sampling and the reconstruction of star dune evolution in general.
Gesehen am 10.10.2024
Online verfügbar: 18 May 2024, Artikelversion: 18 May 2024